Pooperacní výsledky expandibilní nitroocní cocky ACQUA (Mediphacos) - Nekolová, J; Pozlerová, J; Jirásková, N; Kadlecová, J; Rozsíval, P (Ceska a slovenska oftalmologie, 2008)
PURPOSE: To assess postoperative outcomes of implanted hydrophilic expandable intraocular lenses ACQUA. MATERIAL AND METHODS: One hundred eyes of 75 patients with implanted intraocular lens (IOL) ACQUA were involved. IOLs were implanted during the period 2004 to 2005. The uncorrected visual acuity (UCVA) and the best-corrected visual acuity (BCVA), refractive error and its spherical equivalent (SE) were measured preoperatively and 1 day, 1, 6, 12 months postoperatively. Possible postoperative complications were evaluated as well. The patients were divided into two groups: first group with the age-related macular degeneration (ARMD) and the second one without it. RESULTS: Sixty-five patients (90 eyes) finished the one-year follow-up period. Preoperative UCVA was 0.23 +/- 0.19, BCVA 0.43 +/- 0.23 and SE + 0.15 +/- + 2.06 D (dioptres). Statistically significant differences between UCVA and BCVA one day and one month postoperatively were established. Six months after the operation and later on, the mean UCVA and BCVA were 0.61 +/- 0.26, and 0.82 +/- 0.23 respectively in all eyes, and 0.67 +/- 0.24, and 0.9 +/- 0.17 respectively in the group of eyes without ARMD. Spherical equivalent was stable during the whole follow-up period, one year after the surgery it was -0.1 +/- 1.12 D in the group of all 90 eyes. The IOL central positioning in the bag was excellent in 86 eyes. Nd:YAG laser anterior capsulotomies were performed in two eyes due to the stricture of the anterior capsule and posterior capsulotomy was performed in one eye due to the fibrous secondary cataract. The ACQUA IOL had to be explanted from one eye because of recurrent acute non-infectious inflammation of the anterior segment. CONCLUSION: According to our experience, the IOL ACQUA Mediphacos shows good and stable postoperative outcomes.
Keywords: refrakce oka; Lens Implantation, Intraocular; lidé středního věku; lidé; senioři nad 80 let; senioři; nitrooční čočky; implantace nitrooční čočky; zraková ostrost; Aged; Visual Acuity; Middle Aged; Refraction, Ocular; Aged, 80 and over; Lenses, Intraocular; Humans